Effects of COVID-19 on the Physical Activity and Mental Health of Medical Students - Usmani, Feroz; Aslam, Amna; Kanwal, Farah (Pakistan Journal of Humanities and Social Sciences, 2023)
To assess the effects of COVID-19 on the physical activity and mental health of medical students in the universities of Lahore. It was a cross-sectional study that was conducted within a time period of two months among the students of public and private universities of Lahore, Pakistan (Services institute of medical sciences (SIMS) and Allama Iqbal medical college (AIMC). Data for the study was collected by administrating questionnaires from medical students. Results were analyzed by using SPSS version 26. Among 170 medical students, most of them were male and 77.65% think that lockdown has affected their physical activities and 58.82% think that lockdown has affected their mental health. There is significant increase in number of people who participated in Indoor games during lockdown from 51.2 % to 81.8 % while there was reduction in no. of people who play Outdoor Games during lockdown from 33.5 % to 8.8 %.61.76% think that lockdown has affected their sports activities, While 38.24% think that lockdown has not affected their sports activities. During lockdown 31.76% of the participants, rarely have the thought that they might have caught coronavirus. 31.76%of the participants never have the thought that they might have caught coronavirus. The health authorities and student affairs department of medical college’s should take proper measures to guide the students on how to improve mental as well as physical health during COVID-19 restrictions.